Procalcitonin, MR-Proadrenomedullin, and Cytokines Measurement in Sepsis Diagnosis: Advantages from Test Combination. (9th November 2015) - Angeletti, Silvia; Dicuonzo, Giordano; Fioravanti, Marta; De Cesaris, Marina; Fogolari, Marta; Lo Presti, Alessandra; Ciccozzi, Massimo; De Florio, Lucia
Abstract : Background . Elevated cytokines levels correlate with sepsis severity and mortality but their role in the diagnosis is controversial, whereas Procalcitonin (PCT) has been largely used. Recently, the mid-regional proadrenomedullin (MR-proADM) has been combined with PCT for diagnosis optimization. In this study the combined measurement of PCT, MR-proADM, and cytokines in patients with sepsis was evaluated. Methods . One hundred and four septic patients and 101 controls were enrolled. Receiver operating characteristic (ROC) analysis and multiple logistic regression were used to evaluate applicant markers for sepsis diagnosis. Markers with best Odds Ratio (OR) were combined, and the posttest probability and a composite score were computed. Results . Based upon ROC curves analysis, PCT, MR-proADM, IL-6, IL-10, TNF- α, and MCP-1 were considered applicant for sepsis diagnosis. Among these PCT, MR-proADM, IL-6, and TNF- α showed the best OR. A better posttest probability was found with the combination of PCT with MR-proADM and PCT with IL-6 or TNF- α compared to the single marker. A composite score of PCT, MR-proADM, and TNF- α showed the best ROC curve in the early diagnosis of sepsis. Conclusion . The combination of PCT with other markers should expedite diagnosis and treatment of sepsis optimizing clinical management.